Prevalence, diversity and applications potential of nodules endophytic bacteria: a systematic review - Hnini, Mohamed; Aurag, Jamal (Frontiers in Microbiology, 2024)
Legumes are renowned for their distinctive biological characteristic of forming symbiotic associations with soil bacteria, mostly belonging to the Rhizobiaceae familiy, leading to the establishment of symbiotic root nodules. Within these nodules, rhizobia play a pivotal role in converting atmospheric nitrogen into a plant-assimilable form. However, it has been discerned that root nodules of legumes are not exclusively inhabited by rhizobia; non-rhizobial endophytic bacteria also reside within them, yet their functions remain incompletely elucidated. This comprehensive review synthesizes available data, revealing that Bacillus and Pseudomonas are the most prevalent genera of nodule endophytic bacteria, succeeded by Paenibacillus, Enterobacter, Pantoea, Agrobacterium, and Microbacterium. To date, the bibliographic data available show that Glycine max followed by Vigna radiata, Phaseolus vulgaris and Lens culinaris are the main hosts for nodule endophytic bacteria. Clustering analysis consistently supports the prevalence of Bacillus and Pseudomonas as the most abundant nodule endophytic bacteria, alongside Paenibacillus, Agrobacterium, and Enterobacter. Although non-rhizobial populations within nodules do not induce nodule formation, their presence is associated with various plant growth-promoting properties (PGPs). These properties are known to mediate important mechanisms such as phytostimulation, biofertilization, biocontrol, and stress tolerance, emphasizing the multifaceted roles of nodule endophytes. Importantly, interactions between nonrhizobia and rhizobia within nodules may exert influence on their leguminous host plants. This is particularly shown by co-inoculation of legumes with both types of bacteria, in which synergistic effects on plant growth, yield, and nodulation are often measured. Moreover these effects are pronounced under both stress and non-stress conditions, surpassing the impact of single inoculations with rhizobia alone.